Variation in the Indian summer monsoon intensity during the Bølling‐Ållerød and Holocene. (2nd August 2013) - Kessarkar, Pratima M.; Purnachadra Rao, V.; Naqvi, S. W. A.; Karapurkar, Supriya G.
<x xml:space="preserve">Abstract</x> [1] Variations in the Indian summer monsoon (ISM) intensity during the last 16.7 ka have been studied using organic carbon (Corg), δ15N of sedimentary organic matter, CaCO3, sediment texture, δ18OC, and Mg/Ca‐derived sea surface temperature, δ18O of sea water and sea surface salinity, in a 14C‐dated sediment core from the eastern Arabian Sea. The δ18O in water and planktonic foraminifera shells off the central west coast of India may be controlled by the ISM intensity as this area receives high precipitation and land runoff. Also, the Corg and CaCO3 contents of sediments and δ15N of sedimentary organic matter may be linked to ISM‐induced productivity and denitrification. The results of the present study reveal that between 16 and 15.2 ka BP, the ISM was weak with minor fluctuations and started intensifying around 15.2 ka BP, at the onset of the Bølling‐Ållerød (B‐A) event. The B‐A event is characterized by higher water column denitrification rates comparable to the present day. The ISM signatures observed in the δ18OC record of B‐A event compare well with those from Timta cave of the western Himalayas and also the Asian summer monsoon signatures from the Hulu caves in China and warming signatures in Greenland Ice Sheet Project 2 (GISP2) suggesting atmospheric teleconnections through Intertropical Convergence Zone. The boundary between the Younger Dryas and the Holocene is discernible with small episodes of abrupt events of increased ISM intensity. This decrease in δ18OC values at ~11.8 ka BP is contemporary with June solar insolation maximum at 30° north and the increase in methane in the GISP2 ice core supporting episodes of warmer climate and increase in ISM intensity. The ISM seems to have been most stable between 7 and 5.6 ka BP. The core exhibits periodicity of 500 years that is comparable to the Atlantic water formation and the Chinese monsoon.